The Effects Of Job Increments, Remuneration On Job Performance With Job Comfort As Moderation Study Demak District Drinking Water Company - Aditya Angger Wibowo (International Forum of Researchers and Lecturers, 2024)
For a company to achieve its goals, the human resource aspect must be competitive. Human resource performance is the spearhead of this achievement. Therefore, the company must provide work comfort to employees so that their performance is optimal and maximum. The purpose of this study aims to analyse the extent of the effects of job increments and remuneration on job performance through job comfort. The effect of job increments and remuneration on job comfort directly or indirectly through moderating variables. The population in this study totalled 136 people. With 120 respondents taking the sempel. The sampling technique uses proportional random sampling method. The data analysis method uses Structural Equation Modeling (SEM). The results of the study are job increments affect job comfort, remuneration affects job comfort, job increments affect job performance, remuneration affects job performance, job comfort affects job performance, job increments have no effect on job performance through job comfort, remuneration affects job performance through job comfort.